2018
DOI: 10.1177/2045893218755979
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy targeting the right ventricle in pulmonary arterial hypertension: is it a potential avenue of therapy?

Abstract: Pulmonary arterial hypertension (PAH) is an incurable disease characterized by an increase in pulmonary arterial pressure due to pathological changes to the pulmonary vascular bed. As a result, the right ventricle (RV) is subject to an increased afterload and undergoes multiple changes, including a decrease in capillary density. All of these dysfunctions lead to RV failure. A number of studies have shown that RV function is one of the main prognostic factors for PAH patients. Many stem cell therapies targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…Transplantation of different stem/progenitor cell types, for example, MSCs [ 54 , 55 , 56 , 57 ], induced pluripotent stem cells (iPS) [ 58 ], endothelial progenitor cells (EPCs) [ 59 , 60 , 61 ], and human amnion epithelial cells (AECs) [ 62 ], have effectively prevented, treated, and/or reversed core features of experimental PH and associated lung diseases where RVH occurs. Such cell-based therapies have been effective in providing protective, anti-inflammatory, regenerative, and improved functional outcomes (reviewed in [ 63 , 64 , 65 ]). Herein, we will focus on the application of MSC-based approaches in experimental PH.…”
Section: Mesenchymal Stem/stromal Cell (Msc) Based-therapies In Exmentioning
confidence: 99%
“…Transplantation of different stem/progenitor cell types, for example, MSCs [ 54 , 55 , 56 , 57 ], induced pluripotent stem cells (iPS) [ 58 ], endothelial progenitor cells (EPCs) [ 59 , 60 , 61 ], and human amnion epithelial cells (AECs) [ 62 ], have effectively prevented, treated, and/or reversed core features of experimental PH and associated lung diseases where RVH occurs. Such cell-based therapies have been effective in providing protective, anti-inflammatory, regenerative, and improved functional outcomes (reviewed in [ 63 , 64 , 65 ]). Herein, we will focus on the application of MSC-based approaches in experimental PH.…”
Section: Mesenchymal Stem/stromal Cell (Msc) Based-therapies In Exmentioning
confidence: 99%
“…There have been multiple cell transplantation preclinical studies for RV dysfunction with various cell types, animal models, and administration methods [44,45]. However, so far, none of them have achieved clinical application.…”
Section: Plos Onementioning
confidence: 99%
“…Indeed, recent preclinical studies suggested that regenerative cell-based therapies, gene therapies ( Fig. 4 ), and epigenetic medicines may offer a new perspective in the treatment of PAH ( Baliga et al, 2011 ; Brouwer et al, 2013 ; Ghofrani et al, 2009 ; Loisel et al, 2018 ).…”
Section: Emerging Therapiesmentioning
confidence: 99%